2021
DOI: 10.1111/jdv.17732
|View full text |Cite
|
Sign up to set email alerts
|

Value of cemiplimab in progressive metastatic cutaneous squamous cell carcinoma after kidney transplantation: a case report

Abstract: Cutaneous squamous cell carcinoma (CSCC) is the most frequent post‐transplant tumour entity resulting from immunosuppression treatment that is needed to prevent organ rejection. Solid organ transplant (SOT) recipients are at higher risk for CSCC and vulnerable for aggressive disease or a fatal course. Here, we report on a case of post‐kidney transplant metastatic CSCC, demonstrating efficacy of cemiplimab in achieving complete remission after previous disease progression under cetuximab treatment. Unfortunatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Well known side effects of immune checkpoint inhibitors are the development of immune related adverse events. In the case series of Tsung et al, 2 of the 7 SOTR developed irAE and one case study showed severe life-threating pneumonitis after cemiplimab treatment for advanced cSCC (14,25). In our patient cohort only one patient developed low-grade skin toxicity without the need to withhold cemiplimab, with an ongoing tumor response to cemiplimab.…”
Section: Discussionmentioning
confidence: 53%
“…Well known side effects of immune checkpoint inhibitors are the development of immune related adverse events. In the case series of Tsung et al, 2 of the 7 SOTR developed irAE and one case study showed severe life-threating pneumonitis after cemiplimab treatment for advanced cSCC (14,25). In our patient cohort only one patient developed low-grade skin toxicity without the need to withhold cemiplimab, with an ongoing tumor response to cemiplimab.…”
Section: Discussionmentioning
confidence: 53%
“…However, EGFR inhibitors are not approved for cSCC 1 and evidence for their use is limited. 18 Most studies show poor durability of response for both chemotherapy and EGFR inhibitors in metastatic cSCC. 19,20 In melanoma, ICI is established as the first-line systemic treatment in adjuvant and metastatic settings in the ICP, with the alternative option of BRAF -/MEKtargeted inhibition in patients with melanomas that harbor a BRAF V600E mutation.…”
Section: The Role Of Ici For Cutaneous Cancers In Immunocompetent Pat...mentioning
confidence: 99%
“…Immunological risk is dependent on transplanted organ, time since transplantation, recipient age, a history of rejection, the presence of donor-specific antibodies, and HLA-matching at time of transplantation. 18,89…”
Section: Modification Of Immunosuppressionmentioning
confidence: 99%
See 1 more Smart Citation